Analisa Segmentasi Pasar Rumah Sakit Umum Mitra Delima - Anisa Ramadhani Kusumastiti; Nofita Dwi Harjayanti; Tita Hariyanti (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this study was to determine the market segmentation X Hospital so as to determine the focus of the marketing will be done. The market segmentation is important to understand the hospital’s target market. The aim of implement hospitals market segmentation is to focus more on marketing in order to set priorities in serving patients optimally. Market segmentation has not been analyzed and documented. The market segmentation is done by classifying patients based on geographic segmentation, demographic, psychographic and behavioral patient's identity using the form contained in the registration section. Data inputted using a computer program to obtain a predetermined percentage segmentation then analyzed.